CAN WIDE ROADS BE A SOLUTION TO THE TRAFFIC PROBLEM? (British Journal of Global Ecology and Sustainable Development, 2024)
Anyone who travels abroad compares their country and the conditions there. I had such an opportunity during my trip to Turkey. For example, I tried to compare the roads of the two countries.